ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI DI KEK MANDALIKA - Awan Syapii, Andi; Baehaqi, Baehaqi; Cahyani, Mimi (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2025)
Interest rates are also a factor that influences investment development. Low interest rates allow investors to invest their capital in an area, especially the Mandalika SEZ in the Central Lombok Regency area. High economic growth makes a positive impression on investors, this could be because economic growth can reflect the prosperity of a region because with economic growth the purchasing power of the community increases, this will be a good investment opportunity for investors. This research aims to see the influence of economic growth, inflation and interest rates on investment value in the Mandalika District, Central Lombok Regency. This research is quantitative research with an associative approach. The analysis used is multiple linear regression analysis. The results of this research are that the economic growth variable (x1) has a significant effect on investment in the Mandalika SEZ, Central Lombok Regency (y). This can be seen from the calculated t value > t table. The inflation variable (x2) does not have a significant effect on investment in the Kek Mandalika area, Central Lombok district. This is proven by the calculated t value being smaller than the table t value. The interest rate variable (x3) has a significant effect on investment in the Mandalika Islands area. This is proven by the calculated t value of the interest rate variable being greater than the t table value. together the variables of economic growth, inflation and interest rates have a significant effect on investment in the Mandalika District, Central Lombok Regency, this is proven by the calculated f value being greater than f table (15.749>3.71).